Effect of Trihexiphenidyl and Procyclidine for the management of resting tremor (Bangladesh Medical Journal, 2016)
Parkinsons disease is the main etiology of resting tremor but may also rarely occur in Essential Tremor, Multiple System Atrophy & Progressive Suprneuclear Palsy. Levodopa improves bradykinesia, rigidity and other commonly associated symptoms. When resting tremor is the predominant presenting symptom of Parkinson's disease or when tremor persists despite adequate control of other parkinsonian symptoms with low dosages of levodopa, an anticholinergic agent such as trihexyphenidyl or Procyclidine may be the treatment of choice. This prospective interventional study was carried out in the department of Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka from March, 2014 to June, 2014 with the intention to outline effectiveness, similarities and differences between Trihexyphenidyl and Procyclidine in alleviating resting tremor. For Parkinsons disease, patients presenting with predominant tremor but minimal bradykinesia and rigidity were purposively selected for the study. Resting tremor was assessed by united parkinsons disease rating scale (UPDRS). A total of 30 consecutive patients, both male and female, having resting tremor due to different etiology & attending both indoor and outpatient department of Neurology, BSMMU were randomized to receive either Trihexyphenidyl or Procyclidine for two weeks. For most of the patients (93%) resting tremor were due to Parkinsons disease and only 7% were due to Essential tremor. In case of Trihexiphenidyl, constancy and amplitude of resting tremor were improved in 60% and 80% respectively. In case of Procyclidine, constancy and amplitude of resting tremor were imoroved 87% and 67% respectively. The difference of improvement between Trihexiphenidyl group and Procyclidine group was not statistically significant.Bangladesh Med J. 2015 May; 44 (2): 72-75